2022
DOI: 10.1017/ehs.2022.31
|View full text |Cite
|
Sign up to set email alerts
|

Rates of ecological knowledge learning in Pemba, Tanzania: Implications for childhood evolution

Abstract: Humans live in diverse, complex niches where survival and reproduction are conditional on the acquisition of knowledge. Humans also have long childhoods, spending more than a decade before they become net producers. Whether the time needed to learn has been a selective force in the evolution of long human childhood is unclear, because there is little comparative data on the growth of ecological knowledge throughout childhood. We measured ecological knowledge at different ages in Pemba, Zanzibar (TZ), interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Our results indicate that childhood is a not time for idling, or just a by-product of other selective pressures, as suggested by early hypotheses [8]. On the contrary, we show that childhood is an active period during which individuals engage, sometimes very successfully, in a variety of activities, which promotes knowledge acquisition [32]. Learning can still be an important reason for the evolution of childhood, however, we point to the fact that the pathways by which knowledge impacts results, and fitness down the line, can be more complex than expected and implicate the involvement of other individuals.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our results indicate that childhood is a not time for idling, or just a by-product of other selective pressures, as suggested by early hypotheses [8]. On the contrary, we show that childhood is an active period during which individuals engage, sometimes very successfully, in a variety of activities, which promotes knowledge acquisition [32]. Learning can still be an important reason for the evolution of childhood, however, we point to the fact that the pathways by which knowledge impacts results, and fitness down the line, can be more complex than expected and implicate the involvement of other individuals.…”
Section: Discussionsupporting
confidence: 54%
“…Other aspects of the models include the estimation of ecological knowledge using an Item Response Theory model (see Pretelli et al [32] for more details on this tool) and the estimation of missing data for knowledge, height and grip strength according to each individual’s age and sex. Note that even though data points relative to individuals who are missing certain measurements provide no information to the model concerning the specific inference for knowledge, height or grip strength, including these data points still improve the model fit and estimation of the other parameters, informed by the non-missing parts of the data (see electronic supplementary material, S3.2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It offered an advancement over previous studies on rabies that modelled rabies knowledge or understanding using observed data [ 52 ]. This is because knowledge is always latent and can never be fully measured [ 53 ]. Similar approaches have been used in diverse fields to target latent knowledge or ability questions [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because knowledge is always latent and can never be fully measured [ 53 ]. Similar approaches have been used in diverse fields to target latent knowledge or ability questions [ 53 , 54 ]. Our results suggested that latent understanding (dog owners’ overall knowledge of the disease) was positively associated with dog vaccination and tertiary-level education, consistent with a recent report from Nigeria [ 36 ].…”
Section: Discussionmentioning
confidence: 99%